Optimalisasi Program 5s Untuk Menekan Jumlah Gangguan Pada Sistem Jaringan Distribusi 20kv - Nayuan Alamsyah (Jurnal Elektronika dan Teknik Informatika Terapan ( JENTIK ), 2023)
The need for electrical energy every year always increases in accordance with economic growth and community welfare. One of the factors that influence this is the development in the field of industry and business which is growing rapidly. As a leading company in Indonesia, PT. PLN (Persero) always strives to provide the best service to its customers by paying attention to the satisfaction of each customer. The method section is written with a length of 15 – 20% of the length of the article, containing the research design, data collection techniques and data sources and methods of data analysis. The number of feeder disturbances is the number of feeder trips in a year. As for the recap of the number of feeder disturbances from ULP Anyer, namely feeder disturbances at ULP Anyer for the 2018 period as many as 11 times to the feeder, for the 2019 period there were 5 feeder disturbances, and for the 2020 period ULP Anyer obtained zero feeder disturbances. ULP Anyer needs attention as a pilot unit for 5S implementation (perfect ROW, perfect in materials, perfect in construction, perfect in protection, and perfect in inspection) in the PLN area of ??the Customer Service Implementing Unit (UP3), North Banten.